Volumetric absorption illumination induced by laser radiation in a 2D thermoelastic microelongated semiconductor body with temperature-dependent properties - Tayel, Ismail M.; Alebraheem, Jawdat; Mohammed, Mogtaba; Lotfy, Khaled; El-Bary, Alaa A. (Frontiers in Physics, 2023)
In this paper, we construct a new model based on the coupling of thermoelasticity, plasma, and microelongation effect under volumetric absorption of the laser pulse. Three different thermoelasticity theories are applied to construct the new model in a 2D thermoelastic semiconducting medium with temperature-dependent properties. The medium surface is exposed to laser radiation having spatial and temporal Gaussian distribution, in addition, the surface is considered traction free. The general solutions are obtained analytically via Laplace and Fourier transformations, for Laplace inverse, we use the well-known Riemann sum approximation. As an application and consistency validation, Silicon material is used